Respuesta :
Answer:
an = -9 -3(n -1)
Step-by-step explanation:
The explicit formula for an arithmetic sequence with first term a1 and common difference d is ...
an = a1 +d(n -1)
Putting your numbers into the formula gives ....
an = -9 -3(n-1)
Answer:
The required formula is [tex]a_n =-3n-6[/tex].
Step-by-step explanation:
Given : An arithmetic sequence whose common difference is -3, and first term is -9.
To find : Write an explicit formula for an arithmetic sequence ?
Solution :
An explicit formula for an arithmetic sequence is given by, [tex]a_n = a_1 +d(n -1)[/tex]
Where, [tex]a_n[/tex] is the nth term of the sequence
[tex]a_1=-9[/tex] is the first term of the sequence
d=-3 is the common difference
n is the number terms
Substitute the value in the formula,
[tex]a_n =(-9)+(-3)(n -1)[/tex]
[tex]a_n =-9-3n+3[/tex]
[tex]a_n =-3n-6[/tex]
Therefore, the required formula is [tex]a_n =-3n-6[/tex].